2023
DOI: 10.1111/1365-2435.14245
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen load predicts host functional disruption: A meta‐analysis of an amphibian fungal panzootic

Abstract: 1. The progression of infectious disease depends on the intensity of and sensitivity to pathogen infection. Understanding commonalities in trait sensitivity to pathogen infection across studies through meta-analytic approaches could provide insight to the pathogenesis of infectious diseases. The globally devastating amphibian chytrid fungus, Batrachochytrium dendrobatidis (Bd), offers a good case system due to the widely available dataset on disruption to functional traits across species.2. Here, I systematica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 151 publications
(153 reference statements)
0
9
0
Order By: Relevance
“…While biologists often work under the assumption that their study animals lack infections that drive major changes in their morphology, behaviour and physiology (Chretien et al, 2023), most animals are (co)infected by parasitic species at different intensities that may vary in their impacts on hosts (Seguel et al, 2023;Wu, 2023).…”
Section: Future Direc Tionsmentioning
confidence: 99%
See 4 more Smart Citations
“…While biologists often work under the assumption that their study animals lack infections that drive major changes in their morphology, behaviour and physiology (Chretien et al, 2023), most animals are (co)infected by parasitic species at different intensities that may vary in their impacts on hosts (Seguel et al, 2023;Wu, 2023).…”
Section: Future Direc Tionsmentioning
confidence: 99%
“…While many of the above phenotypic changes represent adaptive host responses, they were historically attributed to parasite‐induced host debilitation. Wu (2023) presents a thorough meta‐analysis of the various functional disruptions induced in amphibian hosts by the debilitating chytrid fungus Batrachochytrium dendrobatidis . The analysis indicated that across host species, this infection leads to a higher resting metabolic rate, lower body condition, impaired osmoregulation and altered behaviour in hosts.…”
Section: Mechanisms For Infection‐induced Phenotypesmentioning
confidence: 99%
See 3 more Smart Citations